PENGARUH MODAL, BAHAN BAKU, DAN TENAGA KERJA TERHADAP PRODUKSI KERAJINAN KAYU DI KABUPATEN TABANAN - Winangun, I Gusti Agung Raditya Pasupati; Wenagama, I Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.03.TAHUN.2024, 2024)
Indonesia has a variety of industries, one of which is the handicraft industry. The handicraft industry is a combination of hand skills with artistic values ??and beauty, which is an inseparable part of Indonesian culture. The implementation of production cannot be separated from the production factors used, such as capital, raw materials, and labor. The purpose of this study was to determine how capital, raw materials, and labor affect the wood craft industry in Tabanan Regency. The method used in this research is Random Sampling, in which the selection of wood craftsmen is random because the distribution of wood craftsmen in Tabanan Regency is uneven. The way of collecting data is using a questionnaire. The data analysis technique used is multiple linear regression. Based on the results of research, capital, raw materials, and labor simultaneously have a significant effect on the production of wood crafts produced in Tabanan Regency. Partially, raw materials, and labor have a positive and significant effect on the production of wood crafts produced in Tabanan Regency.